Acute urinary retention caused by seminoma in a case of persistent Mullerian duct syndrome - Jayesh Modi; Deepika Modi; Lira Bachani (Wolters Kluwer Medknow Publications, 2015)
Urinary symptoms have been described secondary to a pelvic mass originating from the ovary, uterus, cervix, prostate, or rectum. Persistent Mullerian duct syndrome is a rare form of intersex disorder, characterized by the presence of uterus and fallopian tubes in an otherwise 46 XY male. We report an adult male with bilateral cryptorchidism and a pelvic mass, who presented with acute urinary retention, and was diagnosed with a seminoma of the right testis, intratubular germ cell neoplasia of the left testis with the presence of Mullerian remnants. Pelvic mass was caused due to seminoma is a rare cause of urinary retention.